2021
DOI: 10.3390/su131810016
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for Corporate Environmental Information Disclosure in China: Public Media Pressure, Local Government Supervision and Interactive Effects

Abstract: Disclosing environmental information is essential for listed firms to demonstrate social conscience. To fulfill government and public media supervision, Chinese listed firms are increasing the quality and quantity of disclosed environmental information. This elicits a new topic of interest: the correlation between media/government supervision and corporate environmental information disclosure (EID). The paper addresses this issue through data analysis and factor correlation study in data from some high-polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Kong et al (2020) reviewed the literature and pointed out that media attention induces firms to exert more effort on environmental protection, especially when there are adverse media reports. Xue et al (2021) empirically found that both media attention and government regulation were significantly positively correlated with environmental information disclosure; notably, the more adverse the effect of government regulation, the more media attention promotes environmental information disclosure. Based on the above analysis, we propose the following hypothesis:…”
Section: Research Hypothesesmentioning
confidence: 98%
“…Kong et al (2020) reviewed the literature and pointed out that media attention induces firms to exert more effort on environmental protection, especially when there are adverse media reports. Xue et al (2021) empirically found that both media attention and government regulation were significantly positively correlated with environmental information disclosure; notably, the more adverse the effect of government regulation, the more media attention promotes environmental information disclosure. Based on the above analysis, we propose the following hypothesis:…”
Section: Research Hypothesesmentioning
confidence: 98%
“…The forest plot output from the meta-analysis based on the random effects model showed (see Figure 6 ) that three studies clearly crossed the zero cut-off, identifying the work of Jiménez-Parra et al (2018) [ 52 ] on enterprise environmental behavior, Aboelmaged (2017) [ 54 ] on enterprise social behavior, and Xue et al (2021) [ 60 ] as outliers. Therefore, these studies were excluded from this study.…”
Section: Methods and Datamentioning
confidence: 99%
“…Numerous studies have also demonstrated that the most convenient way for analysts to obtain corporate information is still through the media [ 73 ], implying that the mining and dissemination of corporate information by analysts can increase the public information available to the media. On the one hand, previous literature also confirms that media attention plays an equally important role in corporate environmental governance [ 10 , 74 ], and the strong pressure of media attention on public opinion can monitor corporations toward improving the quality of their environmental disclosures and, thus, their image in regulating environmental mismanagement [ 75 , 76 , 77 ]. On the other hand, the external public pressure caused by media attention leads to government intervention.…”
Section: Empirical Analysismentioning
confidence: 96%